Toleransi Umat Muslim terhadap Keberadaan Gereja Pantekosta di Surabaya - Maulidah, Robi’atul (Program Studi Studi Agama-Agama, Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2014)
This article discusses about the existence of Pentecostal Church and the impact toward the interreligious harmony in Kandangan. This study aims to depict the history of the establishment of central Pentecostal Church in the village Kandangan, Benowo, Surabaya and along with Moslem respond around it and the impact from the church. This research constitutes descriptive-qualitative research by using case study approach. Theoretical study used by the researcher is a concept of Rainer Forst, Frans Magnis Suseno and Francesco Capotorti. Such findings are first Surabaya central Pantekosta church is a church that has been long standing in Kandangan village since 1980s. It was pioneered by local villagers namely Mrs. Supiyati and others villagers. At that period, there were native citizens. In getting permission, the church’s member came to every villager houses which finally made up in getting permission. Second is actual condition of social life of the Kandangan villagers depicts interreligious harmony among the people, especially between the Pentecostal Church followers and Moslem around the church. Third is about the existence of the church, since it has been built and until now it does not show any negative effect and the relationship between Moslem and Christian in Kandangan goes well.